2019
DOI: 10.1111/nph.15740
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of nitrate uptake under salt stress by ectomycorrhiza with and without a Hartig net

Abstract: Summary Salt stress is an important environmental cue impeding poplar nitrogen nutrition. Here, we characterized the impact of salinity on proton‐driven nitrate fluxes in ectomycorrhizal roots and the importance of a Hartig net for nitrate uptake. We employed two Paxillus involutus strains for root colonization: MAJ , which forms typical ectomycorrhizal structures (mantle and Hartig net), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 91 publications
2
38
0
Order By: Relevance
“…They were observed in only one treatment each where they made up less than 2% of the community, but they were included in subsequent statistical analyses despite the poorly formed Hartig net. Recent research indicates that EM fungi can still carry out critical functions even without a functional Hartig net (Sa et al, 2019). Members of the Heliotiales can form associations with ectomycorrhizas (Nakamura et al, 2018) and it is possible that this is what we observed.…”
Section: Emf Colonization and Community Compositionmentioning
confidence: 52%
“…They were observed in only one treatment each where they made up less than 2% of the community, but they were included in subsequent statistical analyses despite the poorly formed Hartig net. Recent research indicates that EM fungi can still carry out critical functions even without a functional Hartig net (Sa et al, 2019). Members of the Heliotiales can form associations with ectomycorrhizas (Nakamura et al, 2018) and it is possible that this is what we observed.…”
Section: Emf Colonization and Community Compositionmentioning
confidence: 52%
“…Similarly, foliar application of TU improved the grain yield of salt-stressed wheat and its protein concentration more than soil-applied bagasse ash (Seleiman and Kheir, 2018), mainly due to greater N uptake (Garg et al, 2006). Excess salinity causes excessive absorption of individual ions leading to toxicity and retards absorption of other essential plant nutrients leading to nutrient deficiencies (Sa et al, 2019). However, TU improves the mechanisms underlying salt-tolerance by modulating the K+/Na+ ratio and increasing uptake of K + , Ca 2+ , and N in maize plants (Kaya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We utilized the in vitro Populus × canescens–P. involutus system – one of the most frequently used systems for analyses of ectomycorrhizal symbiosis in poplar (Gafur et al ., 2004, 2007; Müller et al ., 2013; Szuba, 2015; Sa et al ., 2019). Populus × canescens microcuttings were propagated in modified Murashige and Skoog (MS) agar media consisting of 1.5% sucrose as described previously (Szuba et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Resource exchange occurs through cell walls (CWs; Balestrini and Bonfante, 2014) mainly via a network of fungal cells present between epidermal and cortical plant cells called the Hartig net (HN) (Smith and Read, 2008). The key role of the HN in N uptake was recently challenged (Sa et al ., 2019), although it is still considered an important surface for resource exchange between symbiotic partners (Smith and Read, 2008; Tschaplenski et al ., 2014). Of similar importance in facilitating resource exchange may be the loosening and changes in the structure of host CWs (Nehls, 2008; Balestrini and Bonfante, 2014; Veneault‐Fourrey et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%